Penerapan Metode Learning Community Dalam Upaya Menumbuhkan Kreativitas Belajar Peserta Didik Kelas 8A - Nehemia Kamakaula; Didik Iswahyudi; Romadhon Romadhon (International Forum of Researchers and Lecturers, 2023)
The low learning creativity of class VIIIA students in PPKn subjects is due to the difficulty of being invited to work together and the learning method is still monotonous. This condition seeks to use learning methods that emphasize aspects of cooperation. This research uses a qualitative approach and an interactive qualitative type of research. Data collection techniques used are observation, interviews and documentation, analysis techniques use triangulation to obtain the validity of data, while data analysis used in research is Reduction, Display and Verification. Based on the results of research in the field that: (1) the application of the community learning method at SMP PGRI Malang to class VIIIA students is said to run quite well because students are able to carry out discussions and work together in doing group assignments. (2) The teacher supervises the course of learning and provides direction during the lesson. To overcome various existing things, students expect various efforts from teachers so that the application of the learning community method can run even better so that it can foster and develop student learning creativity.